Overfishing population characteristics of razor clam, Ensis macha, from Independencia Bay, Peru, in 2004 year - Espinoza, Roberto (2010)
Quantitative monthly samplings, in 2004, were carried out to estimate the density and biomass of Ensis macha (Molina 1782), from Morro Quemado area, Bay Independence, Pisco. The present study analyzes biometric relationships, growth parameters and somatic production using the ELEFAN I routine and the Crisp’s method. During the year 2004 the rate of exploitation (E= 0.69 y-1) was significantly bigger than the values of 2003 and the monthly landings (maximum of 335 t) and fishing effort (maximum of 848 trips) were twice increased. These changes induced in the same year a significant decrease of population mean density (D= 54.13 ind. m-2) and the halfway reduction of somatic production (P= 81.99 gAFDW m-2 y-1) and P/B rate (0.38 y-1) values, regarding the values of the previous year. Also, a significant increment of total mortality rate (2.84 y-1) and the fishing mortality rate (1.97 y-1) were twice increased, regarding the previous year. It is assumed that the population of razor clams already was a overfishing commercial resource in the 2003 and that the increment of fishing pressure in the 2004, particularly during the second semester, intensified its overfishing resource condition.